Functional Foods - Phytochemicals and Health Promoting Potential 2021
DOI: 10.5772/intechopen.96746
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dietary Compounds in Functional Foods on MicroRNAs Expression

Abstract: MicroRNAs (miRNAs) are a class of non-coding endogenous RNA molecules that are involved in post-transcriptional gene silencing via binding to their target messenger RNA, leading to mRNA degradation or translational repression. MicroRNAs can be modulated by several factors including hormones, transcription factors, and dietary compounds. These biologically active compounds have positive impact on the progression of human pathology including non-communicable diseases, which indicating that administration of diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 119 publications
(133 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, these dietary miRNAs have developed into prognostic biomarkers for the diagnosis and prognosis of diseases like cancer, epilepsy, viral infections, neurological illness, cardiovascular disorders, sepsis, diabetes, and muscular disorders [65][66][67][68]. Numerous studies have been reported to determine how dietary miRNAs contribute to the treatment of various human/animal diseases [7,33,47,[65][66][69][70][71][72][73]. Recently dietary miRNAs have been implicated in the treatment of various genetic and non-genetic diseases/ disorders in humans (Figure 3, Table 1).…”
Section: Therapeutic Use Of Dietary Mirnamentioning
confidence: 99%
“…Interestingly, these dietary miRNAs have developed into prognostic biomarkers for the diagnosis and prognosis of diseases like cancer, epilepsy, viral infections, neurological illness, cardiovascular disorders, sepsis, diabetes, and muscular disorders [65][66][67][68]. Numerous studies have been reported to determine how dietary miRNAs contribute to the treatment of various human/animal diseases [7,33,47,[65][66][69][70][71][72][73]. Recently dietary miRNAs have been implicated in the treatment of various genetic and non-genetic diseases/ disorders in humans (Figure 3, Table 1).…”
Section: Therapeutic Use Of Dietary Mirnamentioning
confidence: 99%